2019
DOI: 10.1080/10942912.2019.1614051
|View full text |Cite
|
Sign up to set email alerts
|

Identification and quantification of phenolic compounds of Artemisia herba-alba at three harvest time by HPLC–ESI–Q-TOF–MS

Abstract: The objective of this study was to evaluate the effect of harvest at different times on the chemical composition of phenolic compounds of Artemisia herba-alba. Plant material has been harvested at three times (July, November, and May). Methanolic plant extracts were obtained by means of ultrasound-assisted extraction and then analyzed by HPLC-electrospray ionization-Q-TOF-MS for their phenolic profile. The HPLC allowed the identification of 26 phenolic compounds, 12 of them were identified for the first time f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…One of the most abundant bioactive components of Artemisia herba-alba are phenolic compounds [ 31 ]. Five fractions were collected after extraction.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most abundant bioactive components of Artemisia herba-alba are phenolic compounds [ 31 ]. Five fractions were collected after extraction.…”
Section: Resultsmentioning
confidence: 99%
“…Other factors such as carbohydrates, nutrients, water quality, developmental stage and stress can also affect the amount of phenolic compounds in the plant (Brasileiro et al 2015;Mhamdi et al 2010). Under stress conditions, the plant accumulates phenolic compounds to prepare itself for the lignification process (Souhila et al 2019). Several studies showed that changes in total phenol content in a long time are noticeable, but its diurnal variations not significant (Brasileiro et al 2015;Mhamdi et al 2010;Ozkan et al 2010;Souhila Khademi Doozakhdarreh et al Bulletin of the National Research Centre (2022) (Chan et al 2009;Sellami et al 2013;Kammoun Bejar et al 2011;López et al 2010;Özcan et al 2020;Sathishkumar et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, many plants may allocate more energy and resources to growth and developmental constructs than to the accumulation of secondary metabolites such as phenolic acids during the spring and summer growing seasons in order to grow rapidly [47,48]. In addition, in summer, plants may produce more of other protective compounds, such as soluble sugars and lipids, that are more beneficial to plants against excessive temperatures or drought conditions than phenolic acids [49,50]. And this phenomenon has also been documented in other species, such as figs, Camellia sinensis, and Arabian Lilac (Vitex trifolia var.…”
Section: Changes In the Chemical Constituents In The Leaves Of A Elat...mentioning
confidence: 99%